Effects of particle shape and size on nanofluid properties for potential Enhanced Oil Recovery (EOR) - Tengku Mohd, T. A. (EDP Sciences, 2016)
Application of Enhanced Oil Recovery (EOR) in oil and gas industry is very important to increase oil recovery and prolong the lifetime of a reservoir but it has been very costly and losing properties of EOR agent due to harsh condition. Nanoparticles have been used in EOR application since they are not degradable in reservoir condition and used in smaller amount compared to polymer usage. Commonly, EOR techniques are focusing on increasing the sweep efficiency by controlling the mobility ratio between reservoir fluid and injected fluid. Thus, this research aimed to analyze the nanofluid viscosity at different particle size and shape, volumetric concentration and types of dispersing fluid, as well as to determine the oil recovery performance at different nanofluid concentration. The nanofluid viscosity was investigated at nanoparticle sizes of 15nm and 60nm and shapes of 15nm spherical-solid and porous. Five nanofluid samples with concentration ranging from 0.1wt.% to 7wt.% were used to investigate the effect of volumetric concentration. Distilled water, ethanol, ethylene glycol (EG) and brine were used for the effect of dispersing fluids. Oil recovery was investigated at five different concentrations of nanofluid samples through flooding test. It was found that viscosity of nanofluid increased with decreasing particle size and increasing volumetric concentration. Solid shape particle and increasing dispersing fluid viscosity resulted in higher nanofluid viscosity. The higher the nanofluid concentration, the higher the oil recovery obtained. It can be concluded that nanofluid properties have been significantly affected by the environment and the particle used for potential EOR application.